Validating the Indonesian Version of UWES-17: A Rasch Model Analysis of Work Engagement - Shaleh, Abdul Rahman; Hayat, Bahrul; Samudera, Arung (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
Work engagement is a positive psychology construct widely sought after and developed in various countries. Psychometric validation requires statistical analysis to measure and differentiate individuals across different cultures. This study aims to validate the Utrecht Work Engagement Scale-17 (UWES-17) instrument on hospitality workers in state-owned companies in Indonesia. The study population comprised 3185 individuals, representing various positions and types of hospitality service jobs within the land transportation sector of a state-owned enterprise. A non-probability sampling approach, specifically convenience sampling, was employed, selecting participants based on their accessibility and willingness to participate. The participants, aged between 18 and 62, came from diverse fields and work areas. Analysis of item responses in the test was the Rasch Model with a study focus on item fit and person fit from the UWES-17 Scale. In addition, assumption tests of unidimensionality and local independence were performed to ensure the validity of the measurement model. The scale’s reliability was also assessed to evaluate the instrument’s consistency. The results showed that the items were overall fit, but the criteria for person fit were unmet. This is due to the tendency for uniformity and too many diverse positions and cultural tendencies of state-owned companies. The implication is that further item development and confirmation are needed on the constituent aspects, especially the absorption constituent items. Additionally, developing a more consistent shorter version or discovering other dimensions of work engagement that are specific to collectivist societies may be possible.